Effects of rosuvastatin on ADMA, rhokinase, NADPH oxidase, caveolin-1, hsp 90 and NFkB levels in a rat model of myocardial ischaemia-reperfusion - Burma, Oktay; Onat, Elif; Uysal, Ayhan; Ilhan, Necip; Erol, Deniz; Ozcan, Mete; Sahna, Engin (Clinics Cardive Publ Pty Ltd, 2014)
Aim: Endothelial dysfunction, oxidative stress and inflammation are among the most important mechanisms of ischaemia-reperfusion (I/R) injury. Besides their cholesterol-lowering effects, statins are known to provide protection against myocardial dysfunction and vascular endothelial injury via nitric oxide-dependent mechanisms. The aim of this study was to investigate the effects of rosuvastatin on certain intermediates involved in the generation of nitric oxide (asymmetrical dimethyl arginin, ADMA, caveolin-1 and hsp 90), oxidative stress (rhokinase, NADPH oxidase) and inflammation (NFkB), using an in vivo model of myocardial infarction in the rat. Methods: Adult male Sprague Dawley rats were divided into three groups (control, I/R and I/R after 15 days of rosuvastatin administration). Reperfusion was applied for 120 min following left anterior descending coronary artery ischaemia for 30 min. Caveolin-1, hsp 90 and NFkB levels were evaluated with the quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) and ADMA, rhokinase and NADPH oxidase levels were evaluated with ELISA. Results: While NFkB and hsp 90 levels were higher in the I/R group, their levels were significantly lower in the rosuvastatin group. While ADMA and NADPH oxidase levels significantly increased with I/R, they were lower in the rosuvastatin-treated group, but not statistically significant. Rhokinase levels were significantly lower in the rosuvastatin group. Caveolin-1 levels were not different between the groups. Conclusion: Our results suggest that ADMA, rhokinase, NADPH oxidase, hsp 90 and NFkB could facilitate I/R injury, and rosuvastatin significantly reduced levels of these parameters. These results indicate that rosuvastatin may have a protective role in I/R injury via mechanisms targeting inflammation, endothelial dysfunction and oxidative stress.
Keywords: ischaemia-reperfusion; rosuvastatin; oxidative stress; ADMA; hsp 90; caveolin-1; NFkB; rhokinase; NADPH oxidase